Investigating the function of a pentameric ligand-gated ion channel with molecular simulation - Dämgen, MA (2019)
Pentameric ligand-gated ion channels (pLGICs) are key players in mediating fast neurotransmission. Upon neurotransmitter binding, they undergo conformational changes that lead to the opening of the channel pore, allowing ions to flow in or out of the cell. They are involved in a range of neurological diseases which makes them important drug targets. The glycine receptor (GlyR) is a chloride-selective member of this receptor family, which is an excellent model system, because structures in key functional states are available and it has been extensively characterized experimentally. This thesis therefore seeks to investigate the function of the GlyR as a representative of the pLGIC superfamily with molecular dynamics (MD) simulations with four focal points.